Designing a Split Air Conditioning System Simulator with Heat Loading Variations - Hartono, R. Yudi (Riwayat: Educational Journal of History and Humanities, 2025)
The research design a split AC cooling system simulator aims to simulate the real working system and find out the achievements that occur in the split AC system, for that it is necessary to test the engine laboratory of Qomaruddin University as a supporter of the achievement of a machine and add insight for students who take part in the practice college of machine performance. The discussion in this design there is a calculation of the cooling load, the impact of refrigeration, refrigerant flow rate, power requirements and achievement coefficients. The materials used to design the cooling system simulator room are square tube (holo iron), 10mm gypsum board, and 100 watt bulbs. The equipment used is a split unit 1/3 PK air conditioner, refrigerant used R22, thermometer, pressure gauge, amper meter pliers, cables and O switches. The method used at this design stage includes the design of the cooling system simulator, the design of the material to be used. use and installation of the air conditioner. Retrieval of test data is done with time variants of 5 minutes, 10 minutes, 15 minutes and 20 minutes at the remote control temperature 16c. The test results are analyzed with Microsoft Excel and the results of the analysis are displayed in graphical form.